The Influence of Brand Image and Online Reviews on the YouTube Platform on Interest in Buying Samsung Smartphones - Ebit Bimas Saputra; Agussalim M (Dinasti Publisher, 2023)
Based on the correlation level, this research aims to determine the influence of the independent variable on the dependent variable, namely looking at the influence of Brand Image and online reviews on interest in buying Samsung Smartphones . Meanwhile, the method used is a quantitative method that uses statistical data to explain/counteract research hypotheses. The unit of analysis refers to the level of unity of data collected during subsequent stages of data analysis. In this study, researchers used an organizational analysis unit, where the object of this research was aimed at Samsung smartphone enthusiasts . The following research was carried out using a field study, namely distributing questionnaires via Google form to 110 undergraduate students from the Faculty of Economics, Department of Management, Andalas University. The following research also aims to see how Brand Image and Online Reviews influence the Interest in Buying Samsung Smartphones among Undergraduate Students at the Faculty of Economics, Department of Management, Andalas University. In analyzing the relationship between variables, the following research uses SPSS version 25.0 software .